The potential of amniotic membrane in surgery - current applications - Leśniak, Marek; Kwieciński, Jakub; Błaszczyk, Agnieszka; Fussek-Styga, Urszula; Trojan, Sara; Miszuda, Sławomir; Basiaga, Bartosz; Bednarz, Krzysztof; Szwedkowicz, Agata; Heluszka, Jakub (Quality in Sport, 2023)
This article explores the potential benefits and challenges of using the amniotic membrane in surgical procedures. Amniotic membranes have been shown to possess anti-inflammatory, anti-scarring, and antimicrobial properties, which can promote wound healing and tissue regeneration. They can be utilized in a variety of surgical settings, including ophthalmology, plastic surgery, and orthopedics. However, the use of amniotic membranes also poses certain limitations and risks, such as the potential for immune reactions and disease transmission. The article reviews the current literature on amniotic membrane usage in surgery and discusses the clinical implications and future research directions. In summary, the amniotic membrane represents a promising alternative to traditional surgical approaches, but its benefits and limitations must be carefully weighed and assessed in each individual case.